Cell biology and gene expression profiling during the early biotrophic invasion by the rice blast fungus Magnaporthe oryzae - Kankanala, Prasanna (Kansas State University, 2007)
Rice blast is a major fungal disease on rice, caused by the hemibiotrophic filamentous ascomycete fungus, Magnaporthe oryzae. This disease accounts for 157 million tons of grain loss annually. The fungus produces a specialized cell called appressorium to penetrate the host surface barrier and enter inside. It produces intracellular Invasive Hyphae (IH) that grow form cell to cell to colonize the host. The mechanisms of appressorium formation and host penetration have been studied in detail but the host colonization strategies remain largely unknown. We applied live-cell imaging to characterize spatial and temporal development of IH and plant responses inside successively-invaded rice cells. Early loading experiments with the endocytotic tracker, FM4-64, showed dynamic plant membranes around IH. These hyphae showed remarkable plasticity and recruited plant cell components. IH exhibited pseudohyphal growth and were sealed in plant membrane, termed the Extra-Invasive Hyphal Membrane (EIHM). The fungus spent up to 12 hours in the first cell, often tightly packing it with IH. IH that moved into neighboring cells were biotrophic, although they were initially thinner and grew more rapidly. IH in neighboring cells were wrapped in EIHM with distinct membrane caps at the hyphal tips. Time-lapse imaging showed IH scanning plant cell walls before crossing them, and transmission electron microscopy showed crossing occurring at pit fields. This and additional evidence strongly suggest that IH co-opt plasmodesmata for cell-to-cell movement. Our studies have revealed insights into a novel hemibiotrophic strategy employed by the blast fungus. Few genes have been previously characterized that impact the biotrophic IH. To understand the molecular basis of the biotrophic infection strategy we employed Laser Microdissection (LM) technology to isolate and purify the IH at this early growth stage. We compared the gene expression of these samples with axenically-grown mycelium using M. oryzae whole genome microarrays. We identified several hundreds of infection specific genes. We have shown that LM technology can be used to isolate homogenous cells from the infected rice tissues to study the underlying molecular mechanisms of signaling during disease formation. These studies will be very critical to understand the host-pathogen interactions to eventually develop durable management strategies.
Keywords: Rice blast; Biotrophy; Plasmodesmata; Laser microdissections; Gene expression profiling; Extra invasive hyphal membrane; Agriculture, Plant Pathology (0480)